2022
DOI: 10.3389/fsurg.2022.1025213
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a prognostic model for predicting overall survival of primary adrenal malignant tumor patients: A population-based study with 1,080 patients

Abstract: ObjectivePrimary adrenal malignant tumor is rare. The factors affecting the prognosis remain poorly defined. This study targeted to construct and corroborate a model for predicting the overall survival of adrenal malignant tumor patients.MethodsWe investigated the SEER database for patients with primary adrenal malignant tumor. 1,080 patients were divided into a construction cohort (n = 756) and a validation cohort (n = 324), randomly. The prognostic factors for overall survival were evaluated using univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Many studies have been conducted on the prognosis, diagnosis, and treatment of malignant adrenal tumors. Researchers have found that patient age, the initial stage of diagnosis, and surgical resection might affect the prognosis of patients with adrenal malignancies ( 6 , 21 , 22 ). However, most studies limited the tumor to a single histological type or only studied one prognostic factor and only the OS of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on the prognosis, diagnosis, and treatment of malignant adrenal tumors. Researchers have found that patient age, the initial stage of diagnosis, and surgical resection might affect the prognosis of patients with adrenal malignancies ( 6 , 21 , 22 ). However, most studies limited the tumor to a single histological type or only studied one prognostic factor and only the OS of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were diagnosed as adrenal gland (primary site C74.0) with adrenal cortical carcinoma (ICD-0-3 Hist/behav code 8370) between 2004 and 2015 year. Based on the SEER Combined Summary Stage 2000 (2004–2017), the stage of tumor was restaged as localized only (I), regional lymph nodes involved only (II), regional by direct extension only (III), regional by both direct extension and lymph node involvement (IV) and distant site(s)/node(s) involved (V) [ 24 ]. The inclusion criteria were as followings: (1) Primary tumor site is adrenal gland.…”
Section: Methodsmentioning
confidence: 99%